Pelajaran dari Kasus Onel de Guzman: Telaah Kolaborasi antara Worm I Love You dengan Trojan Barok - Happy Chandraleka (Paradigma, 2008)
Many applications belong to malicious software, such as virus, worm, Trojan horse, Trojan mule, email bomb, and malicious script. However, the prominent ones are virus, worm, and Trojan horse. Each of these software bears different characteristics and manner. Most malicious software attacks are individual ones. Integrated attacks, collaboration between one malicious software with another, seldom happen. This article describes collaboration between I Love You worm with Trojan Barok, both of which are made by Onel de Guzman, a student from Manila.